TEACHERS’ PERSPECTIVE ON THE READING BEHAVIOUR OF PRIMARY ESL LEARNERS IN SJKC CHUNG HUA SEMERA SARAWAK - Melor Md Yunus; Jong Sze Chun (Proceedings of The ICECRS, 2016)
This study attempts to investigate the reading behaviour of primary ESL (English as a Second Language) learners in SJKC Chung Hua Semera Sarawak through the perspective of their teachers in the ESL classroom. To acquire this, interviews were carried out with the teachers to collect qualitative data. A total of 3 ESL teachers were selected from the school to participate in this study. The analysis of the data reveals that majority of the ESL learners spent most of their time reading by skimming and scanning, identifying keywords, applying one-time reading, non-linear reading, and reading selectively. On the contrary, the ESL learners spent less time reading expansively and comprehensively. Since the English language is the learners’ second or third language, they lack confidence and motivation as they face various hindrances in fully understanding and interpreting information in this language. The findings of this study intend to provide a springboard for further researches on the approaches to enhance ESL reading skills. Instructional implications are also discussed.